Dynamic behavior of a two-mass nonlinear fractional-order vibration system - Han, Yu-Xing; Zhang, Jia-Xin; Wang, Yu-Lan (Frontiers in Physics, 2024)
The two-mass nonlinear vocal cord vibration system (VCVS) serves as a mechanical representation of the fundamental vocalization process. Traditional models of the VCVS, which are based on integer-order dynamics, often overlook the impact of memory effects. To address this limitation and enhance the accuracy of simulations, this study incorporates the memory effects of vocal cord vibrations by integrating the Grunwald-Letnikov fractional derivative into the two-mass nonlinear VCVS framework. Initially, a high-precision computational scheme is formulated for the two-mass nonlinear fractional-order VCVS. Subsequently, the model undergoes a comprehensive series of numerical simulations to investigate its dynamic characteristics. The findings reveal that the dynamics of the fractional-order VCVS exhibit a significantly higher complexity compared to the conventional integer-order models, with the emergence of novel chaotic behaviors that were previously unobserved.